Boundary Value Problem for a Heated Nanofluid Flow in the Presence of Magnetic Field - Hriczó, Krisztián (International Journal of Engineering and Management Sciences, 2019)
The aim of this paper is to introduce some new numerical results on the magneto-thermomechanical interaction between heated viscous incompressible magnetic nanofluid and a cold wall in the presence of a spatially varying magnetic field. The governing nonlinear boundary layer equations are converted into coupled nonlinear ordinary differential equations by similarity transformation. The ODE system is solvable numerically for example using higher derivative method. The investigation is focused on the influence of governing parameters corresponding to various physical conditions. Numerical results are exhibited for the dimensionless wall skin friction and for heat transfer coefficients at the wall, along to distributions of the velocity and the temperature.